Ecologia de Paisagens da Bacia Hidrográfica do Córrego Palmital: subsídios ao planejamento ambiental - Santos, João Matheus Dyonisio dos (2022)
Landscape Ecology, a term coined by Carl Troll in 1939, as a discipline and systemic approach serves as a subsidy for the planning and analysis of landscapes and their changes. As a case study for this research, the Córrego Palmital Hydrographic Basin was used as a landscape unit, whose occupation intensifies with the arrival of Italian and Portuguese immigrants in the early 20th century, thus forming a community that interacts with the nature of the place. for over a hundred years, building a duality relationship, where changes are expressed through the typology of land use, through time and in the formation of the current landscape. For this, the analysis of the landscape of the Córrego Palmital Watershed through the characterization of its natural elements, the dynamics of land use and occupation, the construction of the geoecological profile, and the analysis of its composition metrics and changes. Through the metrics of the landscape and its changes in composition for the period of 2006, 2013 and 2020, it was possible to verify the decrease in the areas of backyards and residences, thanks to the productive model adopted by agribusiness, favoring the relationship of leasing land of small owners by the large mills, weakening the cultural and belonging relationships of these owners with the properties, which promotes the homogenization of the landscape and the favoring of land concentration, together with that the homogenization and increase of the impacts arising from the monoculture of sugarcane. Through this diagnosis and analysis, in order to maintain the local culture, economically develop the community and conserve its natural resources, suggesting actions as a way to change the prognosis of the future scenario.